Profil penguasaan konsep siswa pada materi suhu dan kalor dalam peer instructions - Putri Dwi Sundari (PILLAR OF PHYSICS EDUCATION, 2019)
Concepts understanding is important for students in determining the success of their learning. One concept that is considered difficult by students is temperature and heat. Concept understanding can be disabled through learning peer instructions. This research aims to determine the profile of students' concepts understanding in the material temperature and heat. This research is a quasi-experiment with one group pretest-posttest model applied to 33 students of class X MIA 6 of SMA Negeri 1 Krian Sidoarjo. The research instrument used were treatment and measurement instruments. The treatment instruments consisted of syllabus, lesson plans, worksheets, and learning observation sheets. While the measurement instruments consist of pre-class reading assignments and concept tests. The research data were analyzed by determining the pattern of the distribution of students' answers on the concept test. From the results of the study showed that there are 3 patterns of changes in students' answers on the concept test that is from true-false, true-false, false-other false. In addition, after obtaining peer instruction learning, there is an increase of students' physics concepts understanding in the material temperature and heat.